Gender-smart investment to improve access to finance and resilience for women-led agribusinesses - Derenoncourt, Marie Ena; Jaquet, Stephanie (Bioversity International and the International Center for Tropical Agriculture, 2023)
Climate change is increasingly threatening agri-food systems. Extreme events and external shocks are affecting global markets and increasing prices for the most vulnerable members of society with women and minorities disproportionally affected. In that context, improving women-led agribusinesses access to finance is key to improving CSA practice adoption and increasing agri-food system productivity. Yet, women in agriculture, food, forestry and fisheries receive less than 10% of total agriculture investments worldwide. The Gender Accelerator program of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in Senegal aims at addressing gender inequality in access to business acceleration by providing targeted business development in conjunction with CSA and CIS capacity building. This paper presents the project results and our recommendations for improving access to finance and improving resilience for women-led SMEs in agri-food systems. To illustrate this process, we analyze a case study of a woman-led SME in the transformation of cashew nuts. We followed her path of change and scale throughout the project via surveys, interviews and analysis of her business model, including its adaptation to climate change. The results underscore the gender-based inequalities that continue to prevail in Senegalese culture despite progress made through initiatives by women-led cooperatives and private sector actors. Even for formal businesses, access to finance remains complicated. There is a need to create awareness and raise the importance of de-risking investments through capacity building and impact analysis. Adapted innovative financial solutions can be a solution to support investment in women-led agribusinesses.